The Influence of Live Streaming on Flash Sale and ITS Impact on Impulse Buying of Shopee E-Commerce Users in Indonesia - Ridwan Alif Nurfatria; Hakim Ramadhan; Muhammad Rifqi; Adi Setiawan; Misbak (Athena: Journal of Social, Culture and Society, 2024)
This study aims to analyze the influence of Live streaming and Flash sale variables on the Impulse Buying behavior of Shopee E-commerce users in Indonesia. The method used is quantitative with descriptive analysis techniques to explain the characteristics of the sample and inferential analysis techniques using SPSS and AMOS software analysis tools. The study population consisted of Shopee e-commerce users in Indonesia, with a sample of 140 respondents selected by non-probability methods with purposive sampling techniques and analysis methods used in this study namely validity test, reliability test, classical assumption test, cross-tabulation test and path analysis. Data was obtained by distributing google form questionnaires through social media. The results of the analysis show that the existence of Live Streaming and Flash Sale has a positive and significant effect on Impulse Buying. This research provides a deeper understanding of the factors that influence Impulse Buying behavior in the context of Live Streaming and Flash Sale of Shopee e-commerce users. The results of this study can provide guidance for Shopee and other e-commerce parties to design more effective marketing strategies and focus on Flash Sale to increase impulse purchases. The results of the validity test output show that the data of this study is declared valid and the reliability test shows that each variable in this study is declared reliable or consistent. The statistical assumption test shows a positive and significant influence, which means that quality Live Streaming can provide stimulus to the Flash Sale program which is a limited number of offers for a short period of time so that it can encourage users to make impulse purchases or unplanned purchases. The path analysis fit model test shows a match of several samples that can subsidize the population as a whole